pH-responsive theranostic nanoplatform of ferrite and ceria co-engineered nanoparticles for anti-inflammatory - Dou, Yuanyao; Zhang, Yimin; Lin, Caiyu; Han, Rui; Wang, Yubo; Wu, Di; Zheng, Jie; Lu, Conghua; Tang, Liling; He, Yong (Frontiers in Bioengineering and Biotechnology, 2022)
Multiple component integration to achieve both therapy and diagnosis in a single theranostic nanosystem has aroused great research interest in the medical investigator. This study aimed to construct a novel theranostic nanoplatform ferrite and ceria co-engineered mesoporous silica nanoparticles (Fe/Ce-MSN) antioxidant agent though a facile metal Fe/Ce-codoping approach in the MSN framework. The resulted Fe3+-incorporated ceria-based MSN nanoparticles possessing a higher Ce3+-to-Ce4+ ratio than those revealed by ceria-only nanoparticles. The as-prepared Fe/Ce-MSN nanoparticles exhibited an excellent efficiency in scavenging reactive oxygen species (ROS), which is attributed to improving the superoxide dismutase (SOD) mimetics activity by increasing Ce3+ content and maintaining a higher activity of catalase (CAT) mimetics via including ferrite ion in nanoparticles. The fast Fe/Ce-MSN biodegradation, which is sensitive to the mild acidic microenvironment of inflammation, can accelerate Fe/Ce ion release, and the freed Fe ions enhanced T2-weighted magnetic resonance imaging in the inflammation site. PEGylated Fe/Ce-MSN nanoparticles in vitro cell models significantly attenuated ROS-induced inflammation, oxidative stress, and apoptosis in macrophages by scavenging overproduced intracellular ROS. More importantly, Fe/Ce-MSN-PEG NPs exhibited significant anti-inflammatory effects by inhibiting lipopolysaccharide (LPS)-induced expression of tumor necrosis factor-α (TNF-α) and interleukin-1 beta (IL-1β) levels in vitro. Additionally, it can promote the macrophages polarization of pro-inflammatory M1 phenotype towards an anti-inflammatory M2 phenotype. Thus, the novel pH-responsive theranostic nanoplatform shows great promise for inflammation and oxidative stress-associated disease treatment.